Spiral scanning improves subject fixation in widefield retinal imaging - Wei, Franklin; Li, Claire Y; Hagan, Kristen; Stinnett, Sandra S; Kuo, Anthony N; Izatt, Joseph A; Dhalla, Al-Hafeez (Optics letters, 2024)
Point scanning retinal imaging modalities, including confocal scanning light ophthalmoscopy (cSLO) and optical coherence tomography, suffer from fixational motion artifacts. Fixation targets, though effective at reducing eye motion, are infeasible in some applications (e.g., handheld devices) due to their bulk and complexity. Here, we report on a cSLO device that scans the retina in a spiral pattern under pseudo-visible illumination, thus collecting image data while simultaneously projecting, into the subject's vision, the image of a bullseye, which acts as a virtual fixation target. An imaging study of 14 young adult volunteers was conducted to compare the fixational performance of this technique to that of raster scanning, with and without a discrete inline fixation target. Image registration was used to quantify subject eye motion; a strip-wise registration method was used for raster scans, and a novel, to the best of our knowledge, ring-based method was used for spiral scans. Results indicate a statistically significant reduction in eye motion by the use of spiral scanning as compared to raster scanning without a fixation target.